Leadership hacks clever shortcuts to boost your impact and results - Stein, Scott 1968- (Wiley, 2022)
Getting more time and finding ways to make things easier is now a new imperative for many people. In a fast-paced world filled with unlimited choices and limited time, business leaders are overwhelmed and looking for solutions to allow them to find short cuts that provide them better results. This book targets the simple tools to get the results they are seeking in less time.
Includes bibliographical references and index. - Online resource; title from PDF title page (EBSCO, viewed July 29, 2022)
Keywords: Leadership; Management; Gestion; management